The Wiley Blackwell Encyclopedia of Race, Ethnicity, and Nationalism 2015
DOI: 10.1002/9781118663202.wberen595
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, Tasks, and Structure in Teams

Abstract: Diversity in teams reflects a variety of demographic, cultural, experiential, and personal differences that individual members possess, which in turn influences team processes and outcomes. Additionally, the effects of team diversity on teamwork are largely contingent upon various factors, both internal and external to teams. Of the myriad of factors potentially affecting the efficacy of team diversity in teamwork, two types of task structure—task complexity and task interdependence—are discussed in this entry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…These findings diverge from previous research in which no indirect relationship was found between the constructs and CK (Kimmerle et al , 2015). For instance, Horwitz (2015) reported that task structure leads to a demand-driven exchange of knowledge and expertise, which then directly influences CK. Moreover, past research has proposed that collaboration motivates individuals to ask questions, explain their insights and exchange knowledge, which might all directly simulate CK formation (Cress and Kimmerle, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These findings diverge from previous research in which no indirect relationship was found between the constructs and CK (Kimmerle et al , 2015). For instance, Horwitz (2015) reported that task structure leads to a demand-driven exchange of knowledge and expertise, which then directly influences CK. Moreover, past research has proposed that collaboration motivates individuals to ask questions, explain their insights and exchange knowledge, which might all directly simulate CK formation (Cress and Kimmerle, 2017).…”
Section: Discussionmentioning
confidence: 99%